T. G. H. James, Pharaoh's People. Scenes from Life in Imperial Egypt, Londres, The Bodley Head-University of Chicago Press, 1984, 282 pp. - Castañeda Reyes, José Carlos (Estudios de Asia y África, 1988)
-